The Impact of Online and Hybrid Learning on Elementary Students’ Foundational Skills in the Post-Pandemic Era - Nur Wahyuni (Ludi Litterarri, 2026)
The COVID-19 pandemic disrupted elementary education globally and raised concerns regarding the decline of students’ foundational skills, particularly literacy and numeracy. In the post-pandemic era, many schools continue to implement online or hybrid learning models, creating the need for empirical evaluation of their impact on elementary students’ academic and non-cognitive development. This study aims to analyze the influence of online and hybrid learning on foundational skills in the post-pandemic context. A quasi-experimental comparative design was employed involving three groups: face-to-face, fully online, and hybrid learning formats. Data were collected through standardized literacy and numeracy tests, motivation questionnaires, classroom observations, and interviews with teachers and parents. Quantitative data were analyzed using ANOVA and effect size calculations, while qualitative data were examined through thematic analysis. The findings indicate that fully online learning tends to be associated with lower foundational skill outcomes, particularly in mathematics, while hybrid learning demonstrates moderate-to-high performance when supported by effective instructional design and meaningful teacher–student interaction. Face-to-face learning remains the most effective for early-grade foundational development. In conclusion, the effectiveness of online and hybrid learning depends on pedagogical quality, contextual support, and equitable access, emphasizing the need for carefully structured hybrid models in post-pandemic elementary education